To What Extent Does Social Media Usage Impact the Ability to Delay Gratification and Attention Span of Teenagers in Mumbai? (British Journal of Multidisciplinary and Advanced Studies, 2023)
The aim of the study is to investigate how social media usage affects the ability of Mumbai teenagers to delay gratification and their attention span. The research predicts that participants with high social media usage will show lower scores on delayed gratification compared to those with low social media usage. In addition, the performance of participants on the Stroop task will differ between those with low and high social media usage. The study uses a combination of meta-analysis and primary data collection, where 41 students from JBCN International School were sampled. The results indicate that high social media usage is associated with a reduced ability to delay gratification, which supports previous studies. The results also show that there is a correlation between the time taken to complete a task and the willingness to defer rewards for greater benefits in the future.